A STUDY ON THE STUDENTS’ ABILITY IN USING EXPRESSION OF SEVENTH GRADE MTs AL-RASYID TANJUNG SIANTAR - Fauziah Sudra; Sri Erma Purwanti; Felci Tria Sauhana (Program Studi Pendidikan Bahasa Inggris, 2021)
The main purpose of this study was to describe the students' ability to use expressions. This research was conducted at the seventh grade of MTs Al-Rasyid Tanjung Siantar from January to February 2021. It is descriptive research and uses total sampling technique in selecting the samples. There are 24 students to be the sample in this research. The data were collected by using a test. The researcher got the result that more than 50 % of the students could use expressions with a total mean score of 72 in the the good category. The total mean score is taken from 5 indicators, that were students' ability In using greeting expression with mean score 80.83 in the good category, leave taking expression with mean score 70.83 in the good category, thank you/ gratitude expression with mean score 75 in the good category, apology expression with mean score 64.16 in the good category, and the students' ability in using self-introduction expression with mean score 69.16 in the poor category. The researcher concluded that the students' ability to use expressions was good, a total score of 72. It means they have a good understanding of expressions, mainly greeting expressions.